Green Budgeting Strategy for Waste Sector Greenhouse Gas Mitigation: A QSPM-Based Approach in Bogor City - Ridwan Adithiansyah; A. Faroby Falatehan; Sri Mulatsih (Journal of Business, Social and Technology, 2026)
Background: The waste sector is a local authority emission source whose mitigation depends on structure of public expenditure rather than its size alone. Objective: This study formulates a budget allocation strategy for the Bogor City Environmental Agency (Dinas Lingkungan Hidup [DLH]) to support greenhouse gas (GHG) emission reduction in the waste sector. Methods: Spending data from 2017–2024 were functionally reclassified into core mitigation, downstream operational, and supporting components to ensure comparability across the 2021 fiscal nomenclature transition. The analysis combined descriptive methods, exploratory multiple linear regression with a COVID-19 dummy variable and a two-year lag (n = 6), and a strategic management framework comprising the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Internal–External (IE) matrix, Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, and Quantitative Strategic Planning Matrix (QSPM) assessed by nine purposively selected expert respondents. Results: Core mitigation activities absorbed only approximately one-sixth of total mitigation spending, while downstream operations dominated budget allocation, and proportion allocated to core mitigation tended to shrink after 2018. Exploratory regression indicated that each additional million rupiah allocated to core mitigation was associated with an approximately 3.2-ton reduction in CO₂-equivalent (CO₂eq) emissions two years later (p = 0.021). The strategic position analysis placed DLH in a hold-and-maintain quadrant. Among seven identified strategies, large-scale organic waste processing through partnerships received the highest QSPM score, with the top four strategies forming a complementary priority cluster. Conclusion: The findings indicate allocative quality, rather than budget volume alone, determines the effectiveness of mitigation spending.